Attitudes regarding a warranty and the expected longevity of dental treatment amongst New Zealand dentists, dental students, and patients: a mixed methods survey - Belinda Liu; David Roessler; Zac Morse (BMC, 2024)
Abstract Objectives To investigate and compare estimates of the longevity of dental treatment, expectations for free remedial treatment, and attitudes about formal dental warranties among dentists, students, and patients. Materials and methods This is a mixed-method cross-sectional questionnaire survey with convenience sampling from dentists, dental students, and patients in New Zealand. A questionnaire was distributed to New Zealand dentists (n = 28) and final-year dental students (n = 27). A separate questionnaire was provided to patients in a university dental clinic (n = 43). Mann-Whitney U, Chi-square and Pearson Correlation, and Binary logistic regression tests were used to test for differences between groups and correlations amongst variables. Qualitative data were analysed thematically. Results Dentists believed that their posterior composite resin restorations would last longer (p = 0.014), would remediate failed crowns for longer (p = 0.002) and would provide longer crown warranties (p = 0.003) compared to students. Patients had higher expectations for restoration longevity and free remediation for failed treatment. Students were generally more willing to provide warranties. Crowns were perceived to be the most warrantable, while endodontic treatment was the least warrantable. Recall attendance, mechanical failure, and adequate oral hygiene were commonly proposed as warranty conditions for restorations and crowns. There was little consensus about complete dentures and endodontic treatment. Conclusions There are significant disparities between the expectations of patients and clinicians regarding treatment longevity and free remediation times. Clinicians, in general, are willing to provide free remediation within a specified time frame, except for endodontic treatment, but are hesitant to provide formal dental warranties.